The Effect of Sharia Monetary Transmission on Murabahah Financing in Sharia Banks in Indonesia - Subekti Khoirun Nikmah; Amalia Nuril Hidayati (Cahaya Abadi Publisher, 2022)
The purpose of the research is to examine the effect of sharia monetary transmission, incuding Bank Indonesia Sharia Certificate (SBIS), Bank Indonesia Sharia Deposit Facility (FASBIS), Third-Party Funds (DPK) on murabahah financing at Sharia banks in Indonesia in the short and long term. The research used a quantitative approach, while the data analysis technique used the error correction model test. The data used are monthly data from 2016-2019. The result of the research showed that, first, in the short-term equation SBIS has a negative and insignificant effect on murabahah financing in Sharia banks in Indonesia, while in the long-term equation SBIS has a positive and significant effect on murabahah financing in Sharia banks in Indonesia. Additionally, in the short term and long-term equation FASBIS has a positive and insignificant effect on murabahah financing in Sharia banks in Indonesia, Indeed, in the short term and long-term equation DPK has a positive and significant effect on murabahah financing in Sharia banks in Indonesia, and lastly, in the short term and long-term equation SBIS, FASBIS, and DPK simultaneously influence on murabahah financing in sharia banks in Indonesia.